Mozambique Urbanization Review : Accelerating Urbanization to Support Structural Transformation in Mozambique - World Bank (World Bank, Washington, DC, 2018)
The Mozambique urbanization review aimed at contributing to the country’s policy and institutional reform agenda on how to harness the full potential of urbanization to promote economic growth and poverty reduction. The study carried out in-depth analyses of the urbanization process, uncovering how urbanization has been influenced by national, regional, and international factors. It identified and analyzed key policy and institutional constraints in increasing the economic benefits of urbanization, including economic, transport, land, and decentralization policies. The study concluded that faster urbanization could increase the pace of economic growth and poverty reduction, but this should not be achieved at the expenses of investments in rural development and agriculture. However, constraints in the creation of productive urban jobs, limited connectivity throughout the system of cities, and dysfunction urban land markets have undermined its economic outcomes. Based on the main findings, the study proposed an emerging national urban reform agenda to enhance the benefits from urbanization in Mozambique focused on: (i) strengthening rural-urban linkages, including reforms to local government finances, enhancing trade and commuting flows; (ii) making urban land systems more equitable and efficient; and (iii) deepening decentralization to provide a broader remit to municipalities for urban planning and domestic resource mobilization.